DISTRIBUTION OF PLASMODIUM FALCIPARUM CHLOROQUINE RESISTANCE TRANSPORTER (PFCRT) AND PLASMODIUM FALCIPARUM MULTIDRUG RESISTANCE 1(PFMDR-1) GENES IN ILORIN NORTH-CENTRAL NIGERIA - Abdulraheem, Jimoh O.; Olalubi, Oluwasogo; Awe, Sunday (FUDMA JOURNAL OF SCIENCES, 2024)
Globally, malaria is a peculiar health challenge particularly in continent of Africa. The ease of developing resistance to anti-malaria drugs by Plasmodium falciparum is a serious impediment towards programs aim at control and elimination of malaria. Consequently, drug efficacy surveillance is desirable to institute adequate and effective treatment policies. In this study, distribution of these genes in Plasmodium falciparum isolates in Ilorin metropolis were investigated. One hundred and three samples collected randomly from 5 hospitals in Ilorin metropolis. The samples were amplified at codon 76 and 86 for Pfcrt and Pfmdr-1 respectively using PCR / Restricted Fragment Length Polymorphism (RFLP). The most prevalent alleles were drug susceptible alleles in the study area (K76 and N86) with 31% and 40% respectively, while drug resistance alleles (86Y) have 13% and the least prevalence 2% was the mixed alleles K76T. UITH has the highest number of susceptible alleles followed by CSC 38% and 46% for K76 and N86 respectively. There are significant differences in the distribution of these alleles and the study sites (P< 0.05). The prevalence of resistance alleles in the area is a welcome development that can be employed for possibility of re-introduction of CQ for the treatment of malaria in the study area which will serve as an advantage over expensive ACT due to fact that it is safe cheap and readily affordable.